2013
DOI: 10.2528/pier13060510
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Model for Wave Propagation in Anisotropic Impedance-Matched Metamaterials

Abstract: Abstract-The propagation of light in an anisotropic impedancematched metamaterial is studied in the frame of geometrical optics. We prove that directions of fieldsD,B andv (ray velocity) are a triad of conjugate directions with respect to the inverse relative dielectric permittivity tensor and constitutes a local basis, whose reciprocal one is formed by directions ofĒ,H fields and wave-vectork. Consequently, both dual bases are intrinsically related to the physical properties of medium. We have identified thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Throughout the paper it will be shown that from the knowledge of tensorε (relative permittivity/ permeability) at any pointr of the wave front (or the ray), the use of direct and reciprocal bases associated with vector fields [6,12] together with ray velocity or phase gradient (found in the first step) the remaining fields may be obtained immediately. In fact, for a given electromagnetic energy density, not all the fields are allowed: only those whose directions form reciprocal bases with respect to relativepermittivity/permeability tensor are possible.…”
Section: Laws Of Evolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Throughout the paper it will be shown that from the knowledge of tensorε (relative permittivity/ permeability) at any pointr of the wave front (or the ray), the use of direct and reciprocal bases associated with vector fields [6,12] together with ray velocity or phase gradient (found in the first step) the remaining fields may be obtained immediately. In fact, for a given electromagnetic energy density, not all the fields are allowed: only those whose directions form reciprocal bases with respect to relativepermittivity/permeability tensor are possible.…”
Section: Laws Of Evolutionmentioning
confidence: 99%
“…Following the procedure given in [6], two conjugate vector bases can be introduced. We choose a direct local basis (P,ē i /{i = 1, 2, 3}) consisting of three unit vectors:…”
Section: Geometrical Structure Of Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in our case the Hodge star depends on material distributions which may be inhomogeneous, making it a function of space. Several formalisms have been proposed in related settings, for example anisotropic materials have been theoretically studied in [8] using classical tensor calculus, while differential forms have been used to recast Maxwell's equations in [9]. However, here GA was chosen due to its clearer geometric interpretation compared to other formalisms.…”
Section: Introductionmentioning
confidence: 99%